A practical and user friendly interface of fuzzy logic rule based system for maintenance policy decision making - Hasan Basari, Abd. Samad (Penerbit UTM Press, 2008)
This paper discusses the use of fuzzy logic rule based (FLRB) to improve and enhance maintenance policy decision making. Currently, the decision provided by maintenance engineers is referring to their expert's opinion based on experience. By using a practical and user friendly FLRB method, better opinion could be derived. There are mainly three basic features of FLRB namely fuzzification, FLRB evaluation and defuzzification. The decision making grid (DMG) is an added feature to classify for example the most important machines by their associated grid of maintenance policy. The grid is developed from the low, medium and high range, the prevention action information and the above mentioned three basic features of FLRB. A real world case study at Palm Oil Mill (POM) plant is used to test the practicality and user friendliness of the technique.